Students' Perceptions of Project-Based Learning in English Courses - Riski Sulistiyaningsih (Journal of English Language and Education, 2026)
Project-Based Learning (PjBL) has been widely applied in English language teaching; however, limited research has examined students’ perceptions in non-English major contexts. This study aims to investigate students’ perceptions of PjBL in English learning, particularly in terms of engagement, collaboration and motivation, communication skill, active participation, and laerning effectiveness. A quantitative approach was employed using a Likert-scale questionnaire administered to 46 first-semester Public Health students. The instrument consisted of 19 valid and reliable items (Cronbach’s Alpha = 0.83), and the data were analyzed using descriptive statistics. The results showed that students had generally positive perceptions of PjBL, with mean scores ranging from 3.26 to 3.32. The highest mean score was found in the collaboration aspect, indicating that students benefited from group-based learning activities. Classroom observations also revealed increased participation. These findings suggest that PjBL can support collaborative learning and student engagement in English classrooms for non-English major students.